2010
DOI: 10.1097/jcn.0b013e3181c83f4b
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Complications Following Sheath Removal With Percutaneous Coronary Intervention

Abstract: Of the 413 patients, 68 (16.5%) had a complication. Sixty-four (15.5%) developed hematomas ranging in size from 1 to 5 cm (n = 35, 8.5%) to greater than 5 cm (n = 29, 7.0%), 6 experienced bleeding (1.5%), 4 (1%) had arteriovenous fistulas, and 3 (0.7%) developed pseudoaneurysms. There were no significant differences for complications using manual, C-clamp, or arterial vascular closure device. Patients with a higher systolic blood pressure (135 vs 129; df = 410, P = .025) and of older age (66 vs 63; df = 411, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 20 publications
2
28
2
1
Order By: Relevance
“…In our study it was found that at first follow-up hemorrhage developed in 11.7% of patients, ecchymosis in 15.9%, and pseudo-aneurysm in 1.0% in no application group. In Botti et al's study [27], ecchymosis was detected in 14.5% of patients, and in Sulzbach-Hoke et al's study [6] pseudo-aneurysm was detected in 1.9% of patients. In a study by Jones et al [26] hemorrhage was seen in 10.0% of patients, hematoma in 12.0%, and ecchymosis in 12.0%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study it was found that at first follow-up hemorrhage developed in 11.7% of patients, ecchymosis in 15.9%, and pseudo-aneurysm in 1.0% in no application group. In Botti et al's study [27], ecchymosis was detected in 14.5% of patients, and in Sulzbach-Hoke et al's study [6] pseudo-aneurysm was detected in 1.9% of patients. In a study by Jones et al [26] hemorrhage was seen in 10.0% of patients, hematoma in 12.0%, and ecchymosis in 12.0%.…”
Section: Discussionmentioning
confidence: 99%
“…When studies were reviewed with regard to complications developing in hospital, it was observed that there were studies which had results of complication rates close to ours (16.5%-17%), less than ours (2.9%), and more than ours (35.7%-65%) [2][3][4][5][6][7][8]. These differences between the results of studies are thought to be originating from differences in methods for providing and maintaining haemostasis, mobilization time, intervention characteristics, and methodological differences like evaluation of complications and selection criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations